The Concept of Teacher Personality and Student Character - Putri, Mayang Dwi Rahma; Nafian, Zidni Ilman; Febriani, Afifah; Sabiruddin, Sabiruddin (Al-kayyis: Journal of Islamic Education, 2024)
Teachers have a big responsibility for keeping the learning process going at school. Whether we realize it or not, besides the tools and everything else related to teaching and achieving educational goals, it turns out that the teacher's personality is a huge factor in how well learning happens. This study aims to determine how much influence a teacher's personality has on students' character in the learning process. This study uses a qualitative method with a library research approach, which is a method of collecting data and materials related to the discussion topic and its issues from library sources, which are then analyzed using the tahlili method, a method of interpreting Quranic verses by describing the meanings contained within them. The results of the study indicate that in performing their duties, teachers have many requirements, one of which is related to the nature of teachers, namely: being authoritative, honest, responsible, fair, sociable or not arrogant, loving their work, able to discipline themselves, forgiving, always wanting to align their knowledge and improve their professional skills with the latest developments in science, and loyal to the nation and state.Teachers should not expect gratitude for their services to students. In carrying out their duties, teachers must act sincerely and selflessly, seeking only the approval of Allah. This implies that a teacher's personality is not merely a teaching style but a foundational element that significantly influences the internalization of values, character development, and students' emotional well-being. Therefore, it is crucial for teachers to cultivate a positive and professional personality as a role model, and schools must provide support to enable teachers to contribute maximally to students' character education.